Diverse and Targetable Kinase Alterations Drive Histiocytic Neoplasms - Diamond, Eli L. (Cancer Discov, 2015)
Histiocytic neoplasms are clonal, hematopoietic disorders characterized by an accumulation of abnormal, monocyte-derived dendritic cells or macrophages in Langerhans Cell (LCH) and non-Langerhans (non-LCH) histiocytoses, respectively. The discovery of BRAFV600E mutations in ~50% of these patients provided the first molecular therapeutisc target in histiocytosis. However, recurrent driving mutations in the majority of BRAFV600E-wildtype, non-LCH patients are unknown, and recurrent cooperating mutations in non-MAP kinase pathways are undefined for the histiocytic neoplasms. Through combined whole exome and transcriptome sequencing, we identified recurrent kinase fusions involving BRAF, ALK, and NTRK1, as well as recurrent, activating MAP2K1 and ARAF mutations in BRAFV600E-wildtype, non-LCH patients. In addition to MAP kinase pathway lesions, recurrently altered genes involving diverse cellular pathways were identified. Treatment of MAP2K1- and ARAF-mutated, non-LCH patients using MEK and RAF inhibitors, respectively, resulted in clinical efficacy demonstrating the importance of detecting and targeting diverse kinase alterations in these disorders.